Learning Obstacle Sebagai Indikator Krisis Konseptual dalam Pembelajaran Bangun Ruang Sisi Datar - Wulandari, Novela; Kusumastuti, Fitri Anisa; Lutfi, Muh. Khaedir (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to identify the Learning obstacles experienced by students in learning quadrilaterals and to analyze how these obstacles indicate the emergence of a conceptual crisis. The method used is a descriptive qualitative approach involving junior high school students as research subjects. Data were collected through diagnostic tests, interviews, and classroom observations to explore students’ learning difficulties in greater depth. The findings show that students still encounter various types of Learning obstacles, including ontogenic, epistemological, and didactical obstacles. These obstacles are evident in students’ inability to understand basic concepts, difficulties in connecting different representations of geometric figures, and the mismatch between teachers’ instructional strategies and students’ learning characteristics. These conditions indicate the presence of a conceptual crisis that may hinder students’ understanding of more complex mathematical concepts. In conclusion, this study emphasizes that the Learning obstacles identified are influenced not only by students’ initial abilities but also by instructional resources and the teaching approaches used. The findings contribute theoretically to the discussion of Learning obstacles in mathematics education and provide practical recommendations for teachers in designing geometry instruction that is more contextual, interactive, and conceptually oriented. Keywords: Conceptual Crisis, Geometry, Learning obstacle, Mathematics Education, Quadrilateral,